BIOENERGYPRODUCTION FROM P ALM OILMILL EFFLUENT BYOPTIMIZING ANAEROBIC DIGESTION USING MICROBIALCOMMUNITYSTRUCTURE - Muhammad Hanif; Hiroyuki Daimon (Jurnal Energi dan Lingkungan (Enerlink), 2013)
The anaerobic digestion is one of the powerful biological methods for bioenergy production. This technology has also been adopted for treating palm oil mill effluent (POME). This work was aimed to optimize the anaerobic digestion system using dynamics microbial lipid community structure. Lipid biomarker profiles used in this work were respiratory quinones (RQ), phospholipid fatty acids (PLF A) and phospholipid ether lipids (PLEL). Anaerobic digestion of POME was run during 300 days operation o oat a mesophilic temperature of 38 C and thermophilic temperature of 55 C and at hydraulic retention time (HRT) of 20 to 40 days in 8L lab-scale tank. A rapid supercritical fluid extraction (SFE) was used to extract the digested POME sludge. Bacterial RQ were determined using ultra performance liquid chromatography (UPLC). Bacterial PLFAand archaeal PLELwere simultaneously determined using gas chromatography-mass spectrometry (GC-MS). Principal component analysis was used to compare multivariate lipid biomarker profiles. The results showed that there was a strong correlation between the changes in lipid biomarker profiles and other anaerobic condition parameters such as pH, HRT and biogas production rate to the anaerobic digestion performance. Optimization of the anaerobic digestion through the determination of microbial lipid community structure is an innovative strategy for bioenergy production effectively from POME.Keywords: bioenergy , POME, anaerobic digestion, microbial community , SFE